1994
DOI: 10.1507/endocrj.41.737
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Changes in Insulin Receptor mRNA Concentrations in Dexamethasone-Treated and Adrenalectomized Rats.

Abstract: Abstract. The relative concentrations of total insulin receptor (IR) mRNA were measured in the epididymal adipose tissue and liver of intact untreated rats, dexamethasone-treated rats, adrenalectomized rats and adrenalectomized rats treated with dexamethasone, using RNA blot assays and a specific IR cDNA probe. Northern blot assays revealed two IR mRNA species of approximately 9.5 and 7.5 kb, in both tissues. Dot-Blot assays followed by densitometry indicated that dexamethasone induced an approximately three-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…While dexamethasone has similar effects in these cell lines, not all tissues responded identically in an intact animal. Dexamethasone treatment of rats induced three-fold INSR expression in the liver, but no change was observed in adipocytes, indicating tissue specificity [84].…”
Section: Evidence For Specific Regulation Of Insr Transcription By Endogenous and Exogenous Stimulimentioning
confidence: 91%
“…While dexamethasone has similar effects in these cell lines, not all tissues responded identically in an intact animal. Dexamethasone treatment of rats induced three-fold INSR expression in the liver, but no change was observed in adipocytes, indicating tissue specificity [84].…”
Section: Evidence For Specific Regulation Of Insr Transcription By Endogenous and Exogenous Stimulimentioning
confidence: 91%
“…A couple of papers have demonstrated that the addition of insulin to cultured hepatocytes or hepatomas decreases the half-life of CYP2E1 mRNA and that inhibition of the insulin signal pathway restores the insulin-mediated decrease in CYP2E1 mRNA levels (Woodcroft and Novak, 1997;Woodcroft et al, 2002). Since adipocytes are one of the main targets of insulin action, and the mRNA level of the insulin receptor in white adipose tissue was as high as in the liver (Leal et al, 1994;unpublished data), it is reasonable to assume that the mechanism reported in the liver or hepatocytes is also functional in adipose tissue. In addition to transcriptional and post-transcriptional regulation, CYP2E1 induction is also regulated at the post-translational level.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well known that DEX augments the abundance of tissue-specific mRNA in several tissues, including liver. [15][16][17][18][19][20] Many effects of DEX on gene expression are mediated through the intracellular glucocorticoid receptor whereas others occur through nontranscriptional means via secondary messenger cascades. 21 DEX binds to the glucocorticoid receptor in the cytoplasm of target cells.…”
Section: Introductionmentioning
confidence: 99%